PROBLEMATIKA IMPLEMENTASI PASAL 491 KUHP BAGI ANGGOTA KELUARGA YANG MENELANTARKAN ORANG DENGAN MASALAH KEJIWAAN (ODMK) DAN ORANG DENGAN GANGGUAN JIWA (ODGJ) DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In Article 491 of the Criminal Code Regarding Public Security Violations Against Persons or Property and Health which explains. Threatened with a maximum fine of seven hundred and fifty rupiah : Whoever is obliged to take care of a madman who is a danger to himself and others, let that person roam unattended. However, in reality family members who intentionally abandon people with mental disorders on the streets are not given criminal sanctions. Until now nothing has been applied from the Pekanbaru City Social Service to this article. The purpose of writing this thesis, namely: first, Implementation of Article 491 of the Criminal Code for Family Members ignore People With Mental Problems (ODMK) and People With Mental Disorders (ODGJ) in Pekanbaru City. Second, Obstacles or Problems in the Implementation of Article 491 of the Criminal Code for Family Members Who Leave People With Mental Problems (ODMK) and People With Mental Disorders (ODGJ) in Pekanbaru City.This type of research can be classified in the type of sociological juridical research, because in this study the author directly conducts research in the place under study in order to provide a complete and clear picture of the problem to be studied, while the population and sample are all parties related to the problem studied in this study, data sources used, primary data, secondary data and tertiary data, data collection techniques in this study with interviews and library data.From the results of the study it can be concluded, first, The implementation of Article 491 of the Criminal Code for Family Members Who Leave People With Mental Problems (ODMK) and People With Mental Disorders (ODGJ) in Pekanbaru City has not gone well because of the ignorance of the Pekanbaru City Social Service regarding the existence of the article.Keywords: Problem – Implementation – Family – Abandonment – People With Mental Problems and People With Mental Disorders